Poetics and politics in Haralds saga Sigurðarsonar - Maria Cristina Lombardi (Filologia Germanica, 2024)
Haralds saga Sigurðarsonar contains many skaldic stanzas composed by different poets and by King Haraldr himself. The aim of this article is to discuss the rhetoric of self-praise and other techniques that Haraldr Sigurðarson and the skalds around him employ, examining the hypothesis of their function as rhetorical speeches. Through analyzing some skaldic stanzas of Haraldr’s, we can observe a great concern and control over the process of memorialization through the correct spreading of information regarding his deeds. As it clearly emerges, Haraldr stresses the strict link between him and his brother St Olaf, in order to present himself as the rightful heir to the Norwegian throne. It is also possible to notice a change between the stanzas composed before and after Haraldr Sigurðarson’s ascent to the throne with respect to the choice and density of kennings and other rhetorical devices, mirroring the passage from being a Viking to becoming a king.